2015
DOI: 10.7717/peerj.1329
|View full text |Cite
|
Sign up to set email alerts
|

No apparent correlation between honey bee forager gut microbiota and honey production

Abstract: One of the best indicators of colony health for the European honey bee (Apis mellifera) is its performance in the production of honey. Recent research into the microbial communities naturally populating the bee gut raise the question as to whether there is a correlation between microbial community structure and colony productivity. In this work, we used 16S rRNA amplicon sequencing to explore the microbial composition associated with forager bees from honey bee colonies producing large amounts of surplus honey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
4
23
5
Order By: Relevance
“…Also noteworthy, is that the taxa represented in different relative abundances in the different landscape types in the current study do not overlap with taxa suggested to trend toward increased prevalence and diversity in more productive colonies (e.g. Lactobacillus species such as Firm‐4) (Horton, Oliver, & Newton, ). Interestingly, Horton et al., () also suggest that overall colony productivity is not consistently correlated with forager gut microbial community.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Also noteworthy, is that the taxa represented in different relative abundances in the different landscape types in the current study do not overlap with taxa suggested to trend toward increased prevalence and diversity in more productive colonies (e.g. Lactobacillus species such as Firm‐4) (Horton, Oliver, & Newton, ). Interestingly, Horton et al., () also suggest that overall colony productivity is not consistently correlated with forager gut microbial community.…”
Section: Discussionmentioning
confidence: 55%
“…Lactobacillus species such as Firm‐4) (Horton, Oliver, & Newton, ). Interestingly, Horton et al., () also suggest that overall colony productivity is not consistently correlated with forager gut microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…Members of Orbaceae and Neisseriaceae such as Gilliamella apicola, Frischella , and Snodgrassella alvi were reported in honey bee guts in several recent studies (Martinson et al, 2012 ; Moran et al, 2012 ; Horton et al, 2015 ; Tarpy et al, 2015 ). These bacteria were described as part of core microbiome of the honey bee gut; however, the functional roles of these bacterial groups are not yet fully understood.…”
Section: Discussionmentioning
confidence: 96%
“…379 In many animals, the gut microbiota form quasi-stable communities, with individual 380 hosts harbouring somewhat predictable communities of different bacterial taxa. These (48,(66)(67)(68). 386 In the honey bee gut, bacterial numbers are highest in the rectum, followed by the 387 ileum, mid-gut and crop (66).…”
mentioning
confidence: 99%
“…In addition, changes in microbiota composition 3 3 2 (dysbiosis) have been associated with the promotion of disease states in humans 3 3 3 and other mammals (64, 65). Dysbiosis in honey bees may be an important correlate 3 3 4 of bee and colony health (48,(66)(67)(68). 3 3 5 In the honey bee gut, bacterial numbers are highest in the rectum, followed by the 3 3 6 ileum, mid-gut and crop (66).…”
mentioning
confidence: 99%